IMPLEMENTASI SCRUM DALAM PENGEMBANGAN WEBSITE SISTEM INFORMASI GO.GRILLED - Daksa Hardistya I Gusti Ngurah; Diatri Indradewi I Gusti Ayu Agung; Surya Mahendra Gede (Universitas Pendidikan Ganesha, 2026)
This study focused on the development of a web-based information system for Go.grilled that implemented the Customer Relationship Management (CRM) concept in order to improve the effectiveness of ordering services and customer data management. The system development process was conducted using the Scrum methodology, which consisted of three main Sprints: system design, customer feature development, and administrative data management. On the customer side, the system provided several features, including a landing page, product and package catalogue, shopping cart, order form, payment methods, upload of transfer proof, and invoice generation. Meanwhile, the administrator side was equipped with login access, a dashboard, product and package management features (CRUD operations and photo uploads), order management, and bookkeeping reports. System testing was carried out using three approaches: white-box testing with the Basic Path Testing technique to examine program logic, black-box testing to verify functional suitability, and User Acceptance Testing (UAT) to evaluate user acceptance. The testing results indicate that all system features function properly and the system is considered suitable for use. The UAT results show that most respondents give good to very good assessments. Therefore, the developed system supports Go.grilled’s business processes in a more structured manner and enhances the management of customer interactions through a CRM-based approach.